ANALISIS VECTOR AUTOREGRESSION (VAR) ANTARA PENGELUARAN PEMERINTAH DAN PERTUMBUHAN EKONOMI DI SUMATERA UTARA TAHUN 1993-2013 - Nurul Izzah (Institut Agama Islam Negeri Padngsidimpuan, 2015)
The government expenditure is the instrument used by the government toincrease regional economy. The objective of the research was to analyze thereciprocal correlation of government expenditure with the economy of NorthSumatera. The research was quantitative analytic with secondary data with thetime series obtained from BPS (Central Bureau of Statistics) of North Sumatera.The data were analyzed by using Vector Autoregression (VAR) analysis withImpulse Response Function (IRF) and Forecast Error Variance Decomposition(FEVD). The result of the research, using lag 1, showed that there was thecontribution of each variable to the variables themselves and to other variables.The variable which had the most effective influence on the economic growth wasgovernment expenditure. The variable economic growth had the most effectiveinfluence on government expenditure on long term.